Elabela: A Novel Biomarker for Right Ventricular Pressure Overload in Children With Pulmonary Stenosis or Pulmonary Atresia With Intact Ventricular Septum - Wang, Jian; Zhou, Yue; Wang, Qingjie; Du, Bowen; Wu, Yurong; Chen, Qian; Zhang, Xi; Lu, Yanan; Chen, Sun; Sun, Kun (Frontiers in Cardiovascular Medicine, 2020)
Background: Assessing right ventricular overload in children is challenging. We conducted this study involving children with pulmonary valvular stenosis (PS) or pulmonary atresia with intact ventricular septum (PA/IVS) to evaluate the potential of a new endogenous ligand of Apelin receptor, Elabela (ELA), as a potential biomarker for right heart overload. Methods: In this prospective cohort study, a total of 118 congenital heart diseases patients with right ventricle outflow tract obstruction were recruited from 2018 to 2019. Among them, 44 isolated PS and 7 PA/IVS patients were selected. Their venous blood was collected, and all patients underwent an echocardiographic examination. Blood was collected from 24 patients with PS after percutaneous balloon pulmonary valvuloplasty. The plasma ELA concentration was measured using enzyme-linked immunosorbent assay. Results: The ELA was significantly associated with the peak transvalvular pulmonary gradient (r=-0.62; p=0.02), thus reflecting the severity of PS or PA/IVS. The ELA significantly increased at 3 days after surgery, when mechanical obstruction of the right outflow tract was relieved. Based on the receiver-operator characteristic curve results, ELA could be a risk factor for duct dependence in patients with critical PS or PA/IVS who are younger than 6 months (AUC: 0.82). Conclusion: ELA concentration was significantly associated with the TVG and severity of PS or PA/IVS, indicating that ELA might be a novel biomarker for right ventricular afterload and reflect the immediate pressure changes in the right heart. Furthermore, ELA might predict duct-dependent congenital heart diseases and is valuable for some echocardiographic indexes.